Define I 1 = ∫ 0 1 cos ( x − x 2 ) { 2 0 1 9 x } d x I 2 = ∫ 0 1 cos ( x − x 2 ) d x n = I 1 I 2 I 3 = ∫ 0 1 { 2 0 1 9 x } n d x
If I 3 can be expressed as B A where A and B are coprime positive integers, find A + B
Notation : { ⋅ } is the fractional part function
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can obtain a more general result: For any integrable function on [ 0 , 1 ] ,
∫ 0 1 f ( x − x 2 ) { n x } d x = 2 1 ∫ 0 1 f ( x − x 2 ) d x
where n is a constant.
Log in to reply
Yup......that is what I did, after seeing the number 2019!!! XD
I think {2019x}+{2019(1-x)}=2018
Log in to reply
We are talking about the fractional part function, not the floor function.
Problem Loading...
Note Loading...
Set Loading...
I 1 = ∫ 0 2 1 cos ( x − x 2 ) { 2 0 1 9 x } d x + ∫ 2 1 1 cos ( x − x 2 ) { 2 0 1 9 x } d x = ∫ 0 2 1 cos ( x − x 2 ) { 2 0 1 9 x } d x − ∫ 2 1 0 cos ( 1 − u − ( 1 − u ) 2 ) { 2 0 1 9 ( 1 − u ) } d u = ∫ 0 2 1 cos ( x − x 2 ) { 2 0 1 9 x } d x + ∫ 0 2 1 cos ( u − u 2 ) { 2 0 1 9 ( 1 − u ) } d u = ∫ 0 2 1 cos ( x − x 2 ) { 2 0 1 9 x } d x + ∫ 0 2 1 cos ( x − x 2 ) { 2 0 1 9 ( 1 − x ) } d x = ∫ 0 2 1 cos ( x − x 2 ) ( { 2 0 1 9 x } + { 2 0 1 9 ( 1 − x ) } ) d x by letting u = 1 − x since u and x are dummy variables
Now, the functions { 2 0 1 9 x } and { 2 0 1 9 ( 1 − x ) } can be rewritten as 2 0 1 9 x − n and 2 0 1 9 ( 1 − x ) − m where n and m are integers such that 0 ≤ 2 0 1 9 x − n < 1 and 0 ≤ 2 0 1 9 ( 1 − x ) − m < 1 .
{ 2 0 1 9 x } + { 2 0 1 9 ( 1 − x ) = 2 0 1 9 x − n + 2 0 1 9 ( 1 − x ) − m = 2 0 1 9 x − n + 2 0 1 9 − 2 0 1 9 x − m = 2 0 1 9 − n − m
We can see that { 2 0 1 9 x } + { 2 0 1 9 ( 1 − x ) } must always be an integer, and since 0 ≤ 2 0 1 9 x < 1 and 0 ≤ 2 0 1 9 ( 1 − x ) < 1 this integer must be either 0 or 1. It can only be 0 if both { 2 0 1 9 x } and { 2 0 1 9 ( 1 − x ) } equal 0, which if possible would only occur in infinitesimal locations which are negligible to the integral, and so { 2 0 1 9 x } + { 2 0 1 9 ( 1 − x ) } = 1 .
∴ I 1 = ∫ 0 2 1 cos ( x − x 2 )
I 2 ∴ n = ∫ 0 2 1 cos ( x − x 2 ) d x + ∫ 2 1 1 cos ( x − x 2 ) d x = ∫ 0 2 1 cos ( x − x 2 ) d x − ∫ 2 1 0 cos ( 1 − u − ( 1 − u ) 2 ) d u = ∫ 0 2 1 cos ( x − x 2 ) d x + ∫ 0 2 1 cos ( u − u 2 ) d u = ∫ 0 2 1 cos ( x − x 2 ) d x + ∫ 0 2 1 cos ( x − x 2 ) d x = 2 ∫ 0 2 1 cos ( x − x 2 ) d x = 2 I 1 = I 1 2 I 1 = 2 by letting u = 1 − x since u and x are dummy variables ∴ I 3 = ∫ 0 1 { 2 0 1 9 x } 2 d x It is easy to see that the function { 2 0 1 9 x } equals 2 0 1 9 x for 0 ≤ x < 2 0 1 9 1 , and then repeats every 2 0 1 9 1 units, repeating a total of 2019 times on the interval [ 0 , 1 ] . Therefore we can write the integral as: I 3 = 2 0 1 9 × ∫ 0 2 0 1 9 1 ( 2 0 1 9 x ) 2 d x = 2 0 1 9 × [ 2 0 1 9 2 3 x 3 ] 0 2 0 1 9 1 = 2 0 1 9 × 2 0 1 9 2 3 × 2 0 1 9 3 1 = 3 1 So the answer is 1 + 3 = 4